2021
DOI: 10.3390/proteomes9030035
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Exposure to Chronic Light–Dark Phase Shifting Circadian Rhythm Disruption on Muscle Proteome in Periparturient Dairy Cows

Abstract: Muscle tissue serves as a key nutrient reservoir that dairy cows utilize to meet energy and amino acid requirements for fetal growth and milk production. Circadian clocks act as homeostatic regulators so that organisms can anticipate regular environmental changes. The objective of this study was to use liquid chromatography tandem mass spectrometry (LC-MS/MS) to determine how chronic circadian disruption in late gestation affected the muscle tissue proteome. At five weeks before expected calving (BEC), multipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In the second study, once per day sampling found no difference in MEL between treatments (data not shown). Evaluation of the effect of PS on mammary development in the second study showed PS treatment decreased mammary development and increased expression of genes in liver and muscle related to oxidative stress (Casey et al, 2021b;McCabe et al, 2021a). One potential explanation of different study findings is the negative effect that PS treatment had on mammary epithelial proliferation and cellular stress in the liver and muscle was potentially negated by the positive effects of greater MEL levels in the first study (Suarez-Trujillo et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…In the second study, once per day sampling found no difference in MEL between treatments (data not shown). Evaluation of the effect of PS on mammary development in the second study showed PS treatment decreased mammary development and increased expression of genes in liver and muscle related to oxidative stress (Casey et al, 2021b;McCabe et al, 2021a). One potential explanation of different study findings is the negative effect that PS treatment had on mammary epithelial proliferation and cellular stress in the liver and muscle was potentially negated by the positive effects of greater MEL levels in the first study (Suarez-Trujillo et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Ruminants rely on gluconeogenesis for 90% of their glucose supply ( Young, 1977 ), and thus minimizing exposures to factors that disrupt circadian clocks may be particularly important in late gestation and early lactation cows, when glucose requirements are particularly high ( Bell and Bauman, 1997 ). Limiting exposure to chronodisruptors may also decrease the risk for developing diseases in the peripartum period, as global analysis of the impact of exposing late gestation dairy cows to circadian disruption on hepatic transcriptome and muscle proteome found a potential for an increased risk of developing fatty liver ( Casey et al 2021 ), and increased oxidative stress in muscle tissue ( McCabe et al, 2021a ).…”
Section: Integration and Reciprocal Regulation Between Circadian And ...mentioning
confidence: 99%